Discovery of sound in the sea: Resources for educators, students, the public, and policymakers - Vigness-Raposa, K.; Scowcroft, G.; Miller, J.; Ketten, Darlene; Popper, A. (2016)
© Springer Science+Business Media New York 2016. There is increasing concern about the effects of underwater sound on marine life. However, the science of sound is challenging. The Discovery of Sound in the Sea (DOSITS) Web site (http://www.dosits.org) was designed to provide comprehensive scientific information on underwater sound for the public and educational and media professionals. It covers the physical science of underwater sound and its use by people and marine animals for a range of tasks. Celebrating 10 years of online resources, DOSITS continues to develop new material and improvements, providing the best resource for the most up-to-date information on underwater sound and its potential effects.